Północnokoreański program nuklearny a regionalny system bezpieczeństwa - Bobowski, Sebastian (North Korea nuclear programme and regional security system, 2009)
Pyongyang’s nuclear ambitions started to be something more than national ability to fulfill energy needs. Over 50 years of incidents, provocations, missile tests and declarations became a component of regime’s survival policy. Number of rounds of six-party talks, involving North Korea, Japan, South Korea, China, Russia and the United States are concentrated on submitting nuclear programmes and disabling nuclear facility of Pyongyang. Economic incentives and normalization of relations with the USA might be a much more effective tool than Bush ’s hostile policies with implicit goal of “regime change” and naming North Korea as a part of an “axis of evil”
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 223-231